Green Start-ups: The New Face Of Green Investing To Realize Sustainable Development Goals. - Cherroun, Reguia; Cherroun, Hacina (جامعة الوادي - University of Eloued, 2022)
: Green start-ups have gained a lot of interest in all governments and states, due to the important role they play in economic growth and jobs creation, as well as in enhancing sustainable development principles, through investing in environmentally friendly projects. However; there are many challenges may face them. This paper aims at highlighting the importance of green start-ups in realizing sustainable development goals, and discussing the main challenges they face, through answering the question: How do green start-ups contribute to achieving sustainable development goals?. The study concluded that there is a significant contribution of green start-ups to sustainable development through their focus on projects that care about the environment, and provide an opportunity to new initiatives for young people, thus contribute in providing job. The study also showed the increasing efforts of governments to encourage this type of enterprises. اكتسبت الشركات الناشئة الخضراء اهتمامًا كبيرًا في جميع الحكومات والدول ، نظرًا للدور المهم الذي تلعبه في النمو الاقتصادي وخلق فرص العمل ، وكذلك في تعزيز مبادئ التنمية المستدامة ، من خلال الاستثمار في مشاريع صديقة للبيئة. ومع ذلك؛ هناك العديد من التحديات التي قد تواجههم. تهدف هذه الورقة إلى إبراز أهمية الشركات الناشئة الخضراء في تحقيق أهداف التنمية المستدامة ، ومناقشة التحديات الرئيسية التي تواجهها ، من خلال الإجابة على السؤال: كيف تساهم الشركات الناشئة الخضراء في تحقيق أهداف التنمية المستدامة ؟. وخلصت الدراسة إلى أن هناك مساهمة كبيرة للشركات الناشئة الخضراء في التنمية المستدامة من خلال تركيزها على المشاريع التي تهتم بالبيئة ، وتوفر فرصة لمبادرات جديدة للشباب ، وبالتالي تساهم في توفير فرص العمل. كما أظهرت الدراسة تزايد جهود الحكومات لتشجيع هذا النوع من المؤسسات.
مقال
Keywords: تنمية مستدامة ; الاستثمار الاقتصاد الاخضر الشركات الناشئة; start-ups; sustainable development; green investing; green start-ups